Melaka food hunter / Mohd Razi Afnan Rosdi … [et al.] - Rosdi, Mohd Razi Afnan; Nazree, Nuzul Najwa; Jungin @ Juggin, Stacy; Mohd Yusof, Yusafika (Division of Research and Industry Linkages, 2017)
Melaka Food Hunter is an application designed for people who visit Melaka. It is essential to everyone who travels to find the best place to eat. Despite finding those places in Facebook, different Blogs and others social media, we create this application solely for the visitors who not very much familiar with the food in Melaka. Our apps come out with four categories which are breakfast, lunch, dinner and desserts. User can choose any of the categories based on their preferences. Then, our apps will list all the recommended places in Melaka. In each places listed, there is rating and comments section where users can rate the place and drop their comments. In addition, user can place their reservation on a certain restaurant directly through our apps. Hence, it will make the visitors convenient.